PENGARUH TOTAL ASSET TURN OVER DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (SUB SEKTOR MAKANAN DAN MINUMAN) PERIODE 2018-2022 - Firdhawati, Mila; Tita Amalya, Neneng (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of Total Asset Turnover (TATO) and Net Profit Margin (NPM) on share prices in manufacturing companies listed on the Indonesian Stock Exchange in the food and beverage sub-sector for the 2018-2022 period. The research method used in this research is a quantitative method and a sampling technique using a purposive sampling method. The population in this study are financial reports in the food and beverage manufacturing industry for the 2018-2022 period. The sample taken was the annual report of the food and beverage manufacturing industry for the period 2018-2022. The data analysis method used is descriptive analysis with classical assumption tests carried out consisting of normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, and Panel Data Regression Tests. Next, hypothesis testing uses the simultaneous f test, partial t test and R2 coefficient of determination test. The results of this research show that partially Total Asset Turnover (TATO) has a positive and significant effect on Stock Prices where the t value is 2.367 > t table 1.694 and the probability value is 0.0241 < 0.05, so it can be interpreted that Ho1 is rejected and Ha1 is accepted. Partially, Net Profit Margin (NPM) has no effect on share prices where the t value is -0.9482 < t table 1.694 with a probability value of 0.3501 > 0.05, so it can be interpreted that Ho2 is accepted and Ha2 is rejected. Meanwhile, simultaneously Total Asset Turnover (TATO) and Net Profit Margin (NPM) have a significant effect on stock prices where in the Fcount test 3.637 > Ftable 3.29 and the significance value is 0.037712 <0.05, it can be interpreted that Ho3 is rejected and Ha3 is accepted. The calculation of the coefficient of determination is 0.1343 or 13.43%. This means that the independent variables Total Asset Turnover (TATO) and Net Profit Margin (NPM) do not make a strong contribution to share prices, while the remaining 86% is influenced by other factors outside of this research. This research was analyzed using Eviews version 10.